Effects of change in age category and weight of equipment on the results of the top Polish athletes practising throwing competitions - Tataruch, R.; Wojnar, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: A change in the weight of equipment associated with the subsequent age categories of the throwing sports poses frequent problems both to the athletes and their coaches. Deterioration of the results resulting from the use of heavier equipment often leads to discouragement of the athletes. In 2002 the change in the rules applied by the International Association of Athletic Federation, which implemented an additional weight of equipment resulted in a milder change in the categories of the sporting age. This research aims to determine the effect of changes in age category and the weight of equipment on the results gained in light athletic throwing competitions. Methods This research involved analysis of the results of the top Polish athletes in throwing competitions (shot put, discus, hammer and javelin) achieved at different ages and with the use of different weighted equipment. The results wer organized into 4 categories - young athlete, early junior, junior and senior. This analysis uses the results of sport ranks gained from the official websites devoted to sport statistics (www.pzla.pl, www.iaaf.com). The main tools of the statistical analysis include the basic descriptive statistics (mean, standard deviation, min., and max.) As a result of the change in the rules identified earlier the analysis here involved only athletes who were affected by these changes. Results / Discussion The dynamic nature and development of sports success in particular athletes is associated not only with the individuality of the competition which is undertaken but also on their age (Iskra et al., 2004, Wojnar et al., 2004). Changes in the weight of throwing equipment suggests that athletes should adapt their training modes to suit this weight change and with sensitivity to age. The results of the analysis indicated that increments in weight can have a significant effect on performance across the different ages. For example, a change in the weight of the equipment associated with successive transfer from the early age to the junior age category results in the deterioration of the results only in the discus. This may be associated with the considerable increase in the weight of the discuss (50 per cent). With adaptation improvement was shown in the second year of the early junior age category in all of the throwing competitions. Performance in javelin throwing did not decrease during the transition from early to late junior categories which reflects the relatively smaller increase in weight of the javelin (14 per cent). In the remaining throwing competitions in the same transition through higher age categories the regression of results was detectable. In the first year of the senior category the results achieved were worse than in the junior category. This deterioration of results in shot put, discus and hammer may be associated with the increase in the weight of the equipment: shot put and hammer (21 per cent) and discus (14.3 per cent). However, it is difficult to attribute the deterioration in the javelin by 3.5 per cent to the equipment weight as the weight did not change. Conclusions In the shot put, discus and hammer throwing events, a change in equipment weight is associated with deterioration of performance in the first year of the successive age categories. A more limited weight change as in the javelin does not have the same negative effect on performance. The results suggest the need to consider these effects at different age categories in the design of appropriate training programs.